A study protocol for individualized prognostic counselling in the palliative phase - Boyd Noël van den Besselaar; A. Sewnaik; M. C. Dorr; A. Hoesseini; J. A. Hardillo; R. J. Baatenburg de Jong; M.P.J. Offerman (BMC Palliative Care)
Abstract Background Head and neck squamous cell cancer (HNSCC) has a poor prognosis, with approximately 25–30% of patients transitioning into the palliative phase at some point. The length of this phase is relatively short, with a median duration of five months. Patients in this stage often have increased prognostic information needs. Unfortunately, predicting individual life expectancy in this phase is particularly challenging, as physicians and patients tend to overestimate survival. To address this issue, we developed the prognostic model OncologIQ Palliative based on user preferences. In this study, we now aim to assess the clinical impact of utilizing this model during counselling. Methods This study will employ both quantitative and qualitative approaches. The primary outcome is decisional conflict and satisfaction with the decision-making process after counselling without (cohort 1) and with (cohort 2) OncologIQ Palliative. Therefore, a prospective sequential cohort study will be conducted. Secondary outcomes include the amount of palliative treatment, overall survival rates, and quality of life. These measurements will be collected after the intervention. Additionally, patients’ perspectives on the decision-making process and proactive care planning, including end-of-life discussions, will be explored through interviews. Discussion By offering more personalized prognostic information for HNSCC patients in the palliative phase, we anticipate a shift towards more patient-centred counselling. This approach can facilitate enhanced end-of-life discussions and better proactive care planning. Patients may experience reduced decisional conflict, feel better prepared for what’s coming, and find assistance in their decision-making process. This could potentially lead to fewer palliative treatments. Overall, these aspects can contribute to a better quality of life and quality of care for HNSCC patients in the last phase of their lives. Trial Registration This study was registered November 18, 2024, on ClinicalTrials.gov: NCT06699316.